Airtraq optical laryngoscope: advantages and disadvantages - (:unkn) unknown (My University, 2013)
Difficult or unsuccesful tracheal intubation is one of the important causes for morbidity and mortality in susceptible patients. Almost 30% of the anesthesia-related deaths are induced by the complications of difficult airway management and more than 85% of all respiratory related complications cause brain injury or death. Nowadays, due to the advances in technology, new videolaryngoscopic devices became available. Airtraq is a novel single-use laryngoscope which provides glottis display without any deviation in the normal position of the oral, pharyngeal or the tracheal axes. With the help of the display lens glottis and the surrounding structures are visualised and under direct view of its tip the tracheal tube is introduced between the vocal cords. In patients having restricted neck motion or limited mouth opening (provided that it is greater than 3 cm) Airtraq offers the advantage of a better display. Moreover the video image can be transfered to an external monitor thus an experienced specialist can provide assistance and an educational course can be conducted simultaneously. On the other hand the Airtraq videolaryngoscopic devices possess certain disadvantages including the need of experience and the time demand for the operator to learn how to use them properly, the rapid deterioration of their display in the presence of a swelling or a secretion and the fact that they are rather complicated and expensive devices. The Airtraq device has already documented benefits in the management of difficult airways, however serial utilization obviously necessitates experience.
Keywords: Humans; Equipment Design; Intubation, Intratracheal; Laryngoscopes; Laryngoscopy; Airway Management; Videotape Recording